Musik Tradislonal Melayu Riau: Refleksi Sosial dan Budaya Masyarakat Melayu - Tengku Ritawati (Jurnal Syntax Admiration, 2025)
Riau Malay traditional music is a cultural heritage that not only possesses high aesthetic value but also plays a crucial role in reflecting the social and cultural life of the Malay community. As a medium of cultural expression, this traditional music instills moral, spiritual, and cultural values. Through instruments such as gambus, rebana, serunai, gendang, and others, as well as lyrics rich in meaning, Riau Malay traditional music serves as a medium for conveying moral messages, strengthening interpersonal relationships, and preserving traditions that are an integral part of community life. Moreover, this music also acts as a symbol of resistance against the influence of globalization, safeguarding local cultural identity, and reinforcing a sense of pride in ancestral heritage. This study employs a qualitative approach with an ethnographic method to understand the role of Riau Malay traditional music in the social and cultural life of the community. The findings indicate that traditional music functions not only as entertainment but also as a means of communication, a reinforcement of social bonds, and an informal educational tool for the Malay community. Thus, Riau Malay traditional music remains relevant as a cultural heritage that must be preserved and developed for future generations.